2000
DOI: 10.1016/s0167-4889(00)00054-9
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor γ1 (PPARγ1) expresses in rat mesangial cells and PPARγ agonists modulate its differentiation

Abstract: Thiazolidinediones, synthetic ligands of peroxisome proliferator-activated receptor gamma (PPARgamma), are reported to have direct beneficial effects on diabetic nephropathy without lowering blood glucose levels in human and rat. We hypothesized these effects of thiazolidinediones might be derived from PPARgamma activation of kidney cells, and we examined the expression of PPARgamma and the effect of PPARgamma agonists, troglitazone and 15-deoxy-delta-prostaglandin J2 (15d-PGJ2), on the proliferation and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…However, subsequently, PPAR-␥ has been confirmed in human kidney (20,21), and several groups have since identified the presence of PPAR-␥ message and protein in major components of the glomerulus, in mesangial cells, and in endothelial cells in animal models (9,22,23). Studies in our laboratory have also confirmed that in several in vitro proximal tubular cell models, these cells also express PPAR-␥ (7,15).…”
Section: Discussionmentioning
confidence: 61%
“…However, subsequently, PPAR-␥ has been confirmed in human kidney (20,21), and several groups have since identified the presence of PPAR-␥ message and protein in major components of the glomerulus, in mesangial cells, and in endothelial cells in animal models (9,22,23). Studies in our laboratory have also confirmed that in several in vitro proximal tubular cell models, these cells also express PPAR-␥ (7,15).…”
Section: Discussionmentioning
confidence: 61%
“…They appear to exert a renoprotective effect in animal models and in vitro studies, which until recently have focused on mesangial cells (2,12,14,26,34). Recent work from our laboratory has demonstrated that PPAR␥ agonists limit LDL-and albumin-induced proinflammatory responses in the human proximal tubule (37) and reduce extracellular matrix production by human cortical fibroblasts (38).…”
Section: Discussionmentioning
confidence: 99%
“…The renoprotective benefit of PPAR␥ agonists is further suggested by studies in nondiabetic models of renal injury, such as the 5/6-nephrectomy model, where activation of PPAR␥ reduced glomerulosclerosis (21). In vitro studies have focused on the use of mesangial cells where PPAR␥ has been well characterized (2,26), with specific PPAR␥ activation exerting an antiproliferative (12,26) and antifibrotic effect, reducing type 1 collagen synthesis and secretion (29) presumed due to a transforming growth factor (TGF)-␤ 1 -dependent mechanism (34). In mesangial cells, pioglitazone has been shown to inhibit TGF-␤-induced fibronectin production (14).…”
mentioning
confidence: 99%
“…In addition to the improved metabolic control, it is possible that PPAR␥ agonists have more direct beneficial actions on the kidney because constitutively expressed PPAR␥ are found in glomeruli, particularly mesangial cells (Asano et al, 2000;Nicholas et al, 2001) and PPAR␥ agonists reduce type I collagen synthesis in cultured glomerular mesangial cells (Routh et al, 2002;Zheng et al, 2002). In addition to directly inhibiting glomerular collagen synthesis, PPAR␥ agonist may also act indirectly, via its anti-inflammatory action.…”
Section: Ppar␥ Agonists Protect the Kidney Better Than Acei 857mentioning
confidence: 99%